P224 Treatment and outcomes of skin and soft tissue NTM infections: an increasingly common and sometimes complex problem. (December 2018) - Kamalanathan, M; Hippolyte, S; Sim You Kuan, D; Milburn, H
Abstract : Introduction: The recently published BTS guidelines on Non-Tuberculous Mycobacteria (NTM) outline management recommendations for pulmonary NTM infection. There has been an increase in reported skin and soft tissue NTM infection (SSI-NTM) over recent years, 1 yet evidence for treatment is largely based on small case series. Objective: To assess treatment and outcome of SSI-NTM cases presenting to a London teaching hospital from January 2013 – December 2017. Methods: All positive NTM cultures from January 2013 to December 2017 from a large London teaching hospital were examined retrospectively. Case notes were reviewed for site of infection, species identification, time to initiate treatment, treatment duration, antibiotic choice, co-existing immunosuppression, complications and recurrence. All HIV, paediatric and pulmonary NTM cases were excluded. Results: 239 patients with NTM were identified. 15 were SSI-NTM (6%). 4 patients were excluded as three have not completed treatment and one was a post-mortem finding (n=11). Details of these 11 cases are shown in the table 1. M. chelonae and M. fortuitum were the most frequently identified (n=6). Treatment duration for M. Marinum, fortuitum and chelonae ranged from 3 to 8 months, and for M. abscessus, intracellularae and kansasii 10 to 18 months. One case was cured with surgical debridement alone. Mean delay was 78 days from symptom onset to treatment initiation. Ten (90%) cases had complete cure with no recurrence. Conclusions: SSI–NTM is under recognised and can present late, potentially following previous multiple attempts of standard antibacterial therapy. It should be considered particularly in cases of immunosuppression, non-healing surgical wounds, injection sites, vascular grafts and cosmetic procedures. Our data suggests that SSI–NTM can be successfully managed with combination antibiotics leading to complete resolution. Clarithromycin may be considered as a single agent for M. chelonae . Surgical debridement and removal of foreign bodies may also aid recovery and limit treatment duration. Further research is needed to guide optimal treatment regimen and duration, as management of these complex cases will become increasingly relevant to the TB and respiratory physician. Reference: Misch E, et al. Skin and soft tissue infections due to non tuberculous mycobacteria. Current Infectious Disease Reports2018;20:6.